2011
DOI: 10.1111/j.1728-4465.2011.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

What Works in Family Planning Interventions: A Systematic Review

Abstract: This study presents findings from a systematic review of evaluations of family planning interventions published between 1995 and 2008. Studies that used an experimental or quasi-experimental design or had another way to attribute program exposure to observed changes in fertility or family planning outcomes at the individual or population levels were included and ranked by strength of evidence. A total of 63 studies were found that met the inclusion criteria. The findings from this review are summarized in tabu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
188
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(197 citation statements)
references
References 66 publications
4
188
1
4
Order By: Relevance
“…In line with previous successes in promoting reproductive health behaviors using mass media [4,5], mobile phones appear to be a feasible option for reaching young people with information about contraception. Mobile phones provide an additional means for communicating reproductive health information and should be considered as a complement to traditional media channels, particularly for reaching young people.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In line with previous successes in promoting reproductive health behaviors using mass media [4,5], mobile phones appear to be a feasible option for reaching young people with information about contraception. Mobile phones provide an additional means for communicating reproductive health information and should be considered as a complement to traditional media channels, particularly for reaching young people.…”
Section: Discussionmentioning
confidence: 70%
“…By contrast, 50% of women and 55% of men aged 15-19 years reported hearing about family planning on the radio, with approximately 25% hearing about it through television or newspaper [3]. Evidence shows that mass media is effective for encouraging use of contraception [4,5], and mass media interventions may effectively reach young people with contraception information.…”
Section: Introductionmentioning
confidence: 99%
“…(Armstrong & Stover, 1994;Aziz & Osman, 1999;Farr, Rivera, & Amatya, 1998;Eren, Ramos, & Gray, 1983;Gardner et al, 2008;Harper, Balistreri, Boggess, Leon, & Darney, 2001;Hoke, et al, 2012;Jejeebhoy, et al, 2011;Lassner, et al, 1995;Mullany, et al, 2010;Parsons et al, 2013;Stanback, Mbonye, & Bekiita, 2007;Warriner, et al, 2006;Warriner, et al, 2011). An increase in the number of providers can lead to significant gains in contraceptive use and may also free up the time of higher-level providers thus allowing them to handle more complex cases (Janowitz, Stanback, & Boyer, 2012;Mwaikambo, Speizer, Schurmann, Morgan, & Fikree, 2011). In line with these studies and WHO recommendations, the province of Quebec passed Bill 90, in 2002, allowing task-shifting between different categories of health professionals (Gouvernement du QuĂ©bec, 2002).…”
Section: Introductionmentioning
confidence: 76%
“…[7][8][9] Analysis findings showed that of any media of Family Planning Information, Education and Communication, televisiom and poster/flyer contributed significant influence to contraceptive use. Women receiving Family Planning message through television were 1.6 times to be contraceptive users.…”
Section: Media Of Family Planning Information Education and Communicmentioning
confidence: 99%